Rheological and Morphological Characterization of Styrene-Isoprene-Styrene (SIS) Modified Asphalt Binder - Mithil Mazumder; Anwar Siddique; Raju Ahmed; Soon-Jae Lee; Moon-Sup Lee (Advances in Civil Engineering)
The demand of strong polymer modified asphalt (PMA) binder is growing due to the increase of traffic and necessity to reduce the early deterioration of pavement due to cracking. In this study, physical and rheological properties of asphalt binder modified with a potential new polymer named styrene-isoprene-styrene (SIS) were investigated through the rotational viscometer (RV), the dynamic shear rheometer (DSR), and the bending beam rheometer (BBR). In order to have a depth understanding on the SIS binder at micro level, micro-morphological observations were conducted using optical microscopy, atomic force microscopy (AFM), environmental scanning electron microscopy (ESEM), and ellipsometry. The result of this study showed that (1) the addition of SIS modifiers increased the viscosity and had a positive effect on rutting resistance of the binder; (2) the addition of 5%, 10%, 15%, and 20% SIS content increased the rutting resistance by 600%, 3000%, 5600%, and 6400%, respectively; (3) the higher the SIS content, the better the cracking resistance of the binder and it is observed to have improved the stiffness by 26% and 51% with the addition of 5% and 10% content of SIS, respectively; (4) AFM images showed the significant correlation between the stiffness and microstructural properties of the binder; (5) the dominance of new oval phase over network structure was evident in ESEM images and observed to have significant correlation to the high stiffness of the binder; and (6) with the percentage increase of SIS modifier, the binder is found to have higher absorption at UV wavelength.